1999
DOI: 10.1016/s0029-7844(98)00343-3
|View full text |Cite
|
Sign up to set email alerts
|

The relation between inter-twin birth weight discordance and total twin birth weight

Abstract: The more favorable the uterine milieu for carrying twins, the smaller the likelihood of discordant twin growth. Birth order of the heavier twin appears to be an integral part of the discordance phenomenon. The similarity of the cohorts suggests that these conclusions are valid for both like and unlike-sexed twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 4 publications
2
18
0
3
Order By: Relevance
“…As a consequence, multiparous women were more likely to deliver larger twins with higher combined twin birthweight. This is in keeping with the report of Blickstein et al, [3,15] which showed that the higher the combined twin birthweight the less likely it was to deliver discordant pairs. In that report, they stated that the uteri that can efficiently nurture twins are associated with increased combined twin birthweight and decreased discordant frequencies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As a consequence, multiparous women were more likely to deliver larger twins with higher combined twin birthweight. This is in keeping with the report of Blickstein et al, [3,15] which showed that the higher the combined twin birthweight the less likely it was to deliver discordant pairs. In that report, they stated that the uteri that can efficiently nurture twins are associated with increased combined twin birthweight and decreased discordant frequencies.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that the lower the combined twin birthweight, the higher the frequency of delivery of birthweight-discordant twins. [3,12] On the other hand, when 25% cut-off point was applied, our frequency (9.6%) compared favorably with 9.3% reported by Ekure and Iroha [16] in Lagos, Nigeria. Further comparison was not possible because the authors of the Lagos study did not state the prevalence using 15% as a cut-off point.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations